Algorithmic Tacit Collusion An Analysis under European Competition Law - Doerr, Adrian (Mohr Siebeck, 2025)
Tacit collusion through pricing algorithms is feasible and increasingly likely - and its effects may be as harmful as those of anticompetitive agreements. By virtue of a new approach set out in this study, Adrian Doerr shows how the law can and should respond within the existing legal framework.
PublicationDate: 20250630
Keywords: Free Riders -- Algorithm -- AI -- institutional imperfections -- time and space -- antitrust -- self-preferencing -- Digital Markets Act -- chatbots -- competition law -- Europe -- Elfes-Urteil -- Professoren-Richter -- Selbstbindung der Rechtsprechung -- PSPP-Urteil -- Handels- und Gesellschaftsrecht, Wirtschaftsrecht, Steuerrecht -- Wirtschaftsrecht -- Wettbewerb, Konzentration -- Europarecht